Epidermal growth factor 61 A/G polymorphism and uterine cervical cancer. Issue 2 (1st February 2007) - Kang, S.; Kim, J. W.; Park, N.-H.; Song, Y.-S.; Park, S.-Y.; Kang, S.-B.; Lee, H.-P.
Abstract : Cervical cancer, the second most common malignancy in women worldwide, is almost invariably associated with infection by human papillomavirus (HPV). However, although many women are infected with high-risk types of HPV, only a subset of infected women will ever develop cervical cancer. Therefore, host genetic factor may play a role in cervical carcinogenesis. Alterations in epidermal growth factor receptor (EGFR) are common events in cervical cancer. Therefore, we hypothesized that a functional polymorphism in the 5′ untranslated region of the epidermal growth factor (EGF) gene, a natural ligand of the EGFR, may play a role in the cervical carcinogenesis and tumor invasiveness. We assessed the possible association between EGF +61 A/G polymorphism and cervical cancer risk in a hospital-based case–control study among 337 Korean women (168 cases, 169 age-matched controls). The frequencies of EGF +61 allele and genotype were not different between cases and controls. We observed increasing trend of lymph node metastasis from A/A homozygous genotype toward G/G homozygous genotype. We did not find any evidence that EGF +61 A/G polymorphism was associated with individual susceptibility of cervical cancer. However, although it was not statistically significant, the increasing trend of lymph node metastasis according to EGF genotype suggests the possibility that individual variance of EGF expression may be associated with cervical cancer invasiveness. We also confirmed that there exists striking ethnic heterogeneity of EGF genotype between Caucasian and East Asian population